Kinematic adjustments in the basketball jump shot against an opponent - Rojas, F. J.; Cepero, M.; Ona, A.; Gutierrez, M. (Ergonomics, 2000)
The aim of this study was to analyse the adjustments in technique made by a basketball player when shooting against an opponent. The subjects used consisted of 10 professional basketball players of the Spanish First Division League. Three-dimensional motion analysis based on video recordings (50 Hz) was used to obtain the kinematic characteristics of basketball jump shots with and without an opponent. It was found that when performing against an opponent the release angle of the ball increased, the flight time was reduced and postural adjustments as determined by the angles at the knee and shoulder increased, all significantly. There were several other non-significant differences that helped to interpret the changes in technique imposed by the presence of an opponent. It was suggested that when shooting with an opponent, players attempted to release the ball more quickly and from a greater height. This strategy will lessen the chance of the opponent intercepting the ball. It was concluded that the differences noted in the technical execution of the skill had implications for practice. It was suggested that training would benefit from practice with an opponent for at least some of the time to condition players to the demands which they were more likely to meet in the game situation.